How reusable are Learning Object Templates : a case study - Kaur, Abtar; Dunning , Jeremy; Kaur , Harvinder; Halimatolhanin, Mohd Khalid (2005)
The purpose of this paper is to share experiences gained at OUM on the reusability of learning object templates creatred collaboratively between Indiana University, Bloomington and Open University Malaysia. These instructional templates include but are not limited to the following: case-study, decision making, intelligent paragraphing, analystical thinking, time-revealed scenarios, matching and empirical observation. In propagating the culture of reusability of templates, subject-matter experts have been trained to create e-content using these templates.